Psychosocial Prenatal Interventions for Teenage Pregnant: A Systematic Review - Simin Montazeri; Setareh Yousefi; Nahid Javadifar (Journal of Family and Reproductive Health)
Objective: Adolescent pregnancy is a pressing public health issue that significantly impacts the health and well-being of young mothers and their children. This systematic review evaluates the effectiveness of psychosocial prenatal interventions for pregnant adolescents, aiming to identify strategies that enhance maternal and neonatal outcomes. Materials and methods: Systematic comprehensive literature search was conducted across PubMed, Web of Science, Scopus, Cochrane, Science Direct, Google Scholar, and Grey Literature. Studies published from 1996 to January 2023 were included if they focused on pregnant adolescents aged 10-22 years and employed randomized controlled trial (RCT) designs. The methodological quality of the included studies was assessed using the Cochrane Risk of Bias 2 tool. Results: Out of 2,450 articles screened, 22 studies met the inclusion criteria, revealing diverse interventions categorized into six main types: antenatal/postnatal educational programs, psychological interventions, home visits, partner support, and social support interventions. Findings indicated that these psychosocial interventions significantly improved maternal mental health, increased prenatal care utilization, and enhanced perinatal outcomes. However, the review highlighted the need for more rigorously designed studies to establish definitive conclusions regarding the most effective intervention strategies. Conclusion: Results show Educational programs focusing on antenatal and postnatal care effectively enhance knowledge, reduce substance abuse, and boost breastfeeding confidence, leading to better pregnancy outcomes. While psychosocial interventions have improved mental health and school attendance. Home visiting programs have positively impacted maternal well-being and parenting skills. Group prenatal care (GPNC) is beneficial, especially for high-risk adolescents, by combining health evaluations with group education and support. Integrating psychosocial support into prenatal care models can help reduce health disparities among adolescent populations.